The effect of a home exercise program prescribed by physiotherapists for pain relief - Arca, Muhammed; Durmaz, Elif Dilara; Satici, Omer; Oguzoncul, Ayse Ferdane (Bayrakol Medical Publisher, 2021)
Aim: The aim of this study was to evaluate the effect of the home exercise program on the pain of physiotherapy and rehabilitation outpatients. Material and Method: The study included 316 patients with low back, neck, shoulder, and knee pain aged 18-65 years. A personal information form was filled out to obtain demographic information about these patients. After exercise training given by the physiotherapists, the pain of the patients was evaluated by a visual analog scale (VAS). After 4 weeks, the patients were called by telephone and questioned whether they were doing the exercises and their pain severity. Results: Among patients, 54,4% (172) were female; 72,8% of the patients with a mean age of 39.85 +/- 13.77 years were married, 40,8% were primary school graduates and 37,3% were housewives. One hundred three patients applied (32,6%) with neck pain, 132 (41,8%) with low back pain, 29 (9,2%) with shoulder pain and 52 (16,5%) with knee pain. It was observed that 55.4% (175) of the patients who were prescribed training did not perform their exercises. Among patients who exercised, 69,6% did not use analgesics in this process. A statistically significant result was found when the before and after exercise VAS data of participants who did exercise and those who did not were compared (p=0.001). Discussion: In the study by Kilic, more than half of the patients who exercised benefited from the exercises they performed and stated that the exercise decreased problems such as pain, locking, fatigue, and limitation of movement due to disease. It was determined that the patients who completed the exercise program had less pain. Regular exercise programs will lead to positive outcomes.
Keywords: Pain; Low back; Neck; Exercise